1999
DOI: 10.1038/sj.ejcn.1600791
|View full text |Cite
|
Sign up to set email alerts
|

The association of energy intake bias with psychological scores of women

Abstract: Objective: Assess the association between reporting bias of dietary energy intake and the behavioral and psychological pro®les in women. Design: At baseline a series of questionnaires were administered to 37 women, (the Marlowe-Crowne Social Desirability Scale, Weinberger Adjustment Inventory (WAI), the Eating Disorder Inventory (EDI), the Restraint Scale and Sorensen-Stunkard's silhouettes). Subjects received training on how to record dietary records. Subjects recorded three days of dietary records to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
1
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 53 publications
4
88
1
6
Order By: Relevance
“…It is generally recognised that eating unhealthy foods is not perceived as a good behaviour, so that snack foods high in sugar and fat and regarded as 'junk foods' could very well be underreported. Weight-conscious individuals, those who frequently diet to lose weight and people concerned with their body image are well known to underreport their food intake 9,11 . In the elderly, memory problems may have affected reporting accuracy, especially as participants were called upon to provide diet information for the previous 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally recognised that eating unhealthy foods is not perceived as a good behaviour, so that snack foods high in sugar and fat and regarded as 'junk foods' could very well be underreported. Weight-conscious individuals, those who frequently diet to lose weight and people concerned with their body image are well known to underreport their food intake 9,11 . In the elderly, memory problems may have affected reporting accuracy, especially as participants were called upon to provide diet information for the previous 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors and behaviours may explain underreporting of energy intake in different populations, including physiological (weight status, body fat) 6,7 , sociodemographic (age, gender) 8 and psychological (social desirability, body dissatisfaction) 9,10 reasons and lifestyle attributes or characteristics (smoking, physical activity) 11 . Some studies have also found differential reporting of macronutrient and nutrient intakes in low energy reporters (LERs) 12,13 .…”
mentioning
confidence: 99%
“…Furthermore, evidence of weight loss during study periods indicates under-eating. This under-eating, along with the under-reporting observed in multiple studies, further complicates the accuracy of dietary recording and assessment methodologies (12) .Other characteristics of under-reporters have been found to be relevant, including dietary restraint, sex, age, percentage body fat and attitudes to food (13)(14)(15) . Buhl et al (16) and Lichtman et al (17) , for example, demonstrated under-reporting levels of between 47 and 59 % in individuals with high dietary restraint.…”
mentioning
confidence: 99%
“…Other characteristics of under-reporters have been found to be relevant, including dietary restraint, sex, age, percentage body fat and attitudes to food (13)(14)(15) . Buhl et al (16) and Lichtman et al (17) , for example, demonstrated under-reporting levels of between 47 and 59 % in individuals with high dietary restraint.…”
mentioning
confidence: 99%
“…O desejo de aceitação social foi definido como a propensão de um indivíduo a fornecer a resposta que ele considera mais desejada e aceita pela sociedade, independentemente dela ser verdadeira (Ballard e Crino, 1988). Geralmente, indivíduos com alto desejo de aceitação social subrelatam comportamentos que são vistos como não desejáveis, como comportamentos anti-sociais, fenômenos psicóticos, uso de drogas ilícitas (Kim e Hill, 2003) e consumo de alimentos doces e ricos em lipídeos (Taren et al, 1999). Já foi encontrado r 2 de 0,194 (p = 0,01) entre o desejo de aceitação social e a seção do Medical Outcomes Study Inventory destinada à saúde física e mental (Bardwell et al, 2001).…”
Section: Introductionunclassified